Review: Biogas Production from Cow Dung and Its Potential in Indonesia - Apriantika, Anellysha Putri; Anwari, Ropi; Janah, Citra Nurul; Syaichurrozi, Iqbal (World Chemical Engineering Journal, 2022)
Cows are ruminant livestock used as a source of food and the economy. Besides that, cows also produce waste, namely cow dung. If cow dung piles up in the open and spreads, it will carry by rainwater to lower places, which can cause soil and air pollution. To reduce cow dung waste can be used as a substrate in an anaerobic digester to produce biogas. Important factors that can affect the biogas rate include pH, temperature, Total Solid (TS) and Volatile Solid (VS) content, and the C/N ratio. The yield of biogas can be optimal with pretreatment and co-digestion. The potential for cow dung can generate electricity of 5,580 kW per day from 18 million head of cattle.